2016
DOI: 10.1002/jsfa.7641
|View full text |Cite
|
Sign up to set email alerts
|

Design of biocompatible immobilized Candida rugosa lipase with potential application in food industry

Abstract: This research has successfully combined an industrially prominent biocatalyst, CRL, and a biocompatible, environmentally suitable carrier, HAP, into an immobilized preparation with improved catalytic properties. The obtained CRL preparation has excellent potential for the food and flavor industries, major consumers in the global enzyme market. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 31 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…Lipases (E.C. 3.1.1.3 triacylglycerol acylhydrolases) are one of the most widely used enzymes for biotechnological applications, such as the production of biodiesel, as well as in the food and pharmaceutical industries. To the best of our knowledge, only a limited number of works investigating the catalytic performance of lipases immobilized on MOFs in general, and on ZIFs in particular, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lipases (E.C. 3.1.1.3 triacylglycerol acylhydrolases) are one of the most widely used enzymes for biotechnological applications, such as the production of biodiesel, as well as in the food and pharmaceutical industries. To the best of our knowledge, only a limited number of works investigating the catalytic performance of lipases immobilized on MOFs in general, and on ZIFs in particular, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Such a low yield could be attributed to inappropriate solvent choice: in Kobata's paper transformations were carried out in polar organic solvents dioxan and acetone. In contrast, our previous study revealed that n-hexane was the most suitable solvent when working with CRL and there are numerous studies confirming the higher esterification activity of CRL in non-polar solvents (Bezbradica, Mijin, Siler-Marinkovic, & Knezevic, 2006, 2007Trbojević Ivić et al, 2016).…”
Section: Fatty Acid Specificity Of Crlmentioning
confidence: 58%
“… 8 , 9 In this perspective, it is an ideal carrier for the immobilized enzyme. 10 13 In these studies, enzyme immobilized onto the porous HAp supports are highly stable. 14 Although immobilized enzymes have many advantages, they still have disadvantages.…”
Section: Introductionmentioning
confidence: 99%